Design and fabrication of a multifocal bionic compound eye for imaging. (27th February 2018) - Cao, Axiu; Wang, Jiazhou; Pang, Hui; Zhang, Man; Shi, Lifang; Deng, Qiling; Hu, Song
Abstract: Miniaturized bionic compound eyes featured with multi-aperture imaging have potential applications in the areas of micro opto-electro-mechanical-system. In this manuscript, we present a novel structure of the bionic compound eye with multiple focal lengths consists of an array of individual lenses with 1000 µ m diameter. The simulation results of the designed multifocal bionic compound eye (MBCE) with two focal lengths of 190 mm and 44.4 mm demonstrate excellent two-order focusing abilities. Moving mask exposure technology was used to fabricate the designed MBCE with the corresponding imaging experiments conducted to validate the two-order imaging ability of the fabricated MBCE. Experimental results revealed that the developed structure has potential applications in diverse optical imaging systems such as three-dimensional imaging and real-time detection of unconfined or fluctuating targets.